2015
DOI: 10.1099/jmm.0.000133
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of silver nanoparticles mediated by atmospheric pressure air cold plasma jet against dermatophyte fungi

Abstract: In an in vitro study with five clinical isolates of dermatophytes, the MIC 50 and MIC 100 values of silver nanoparticles (AgNPs) ranged from 5 to16 and from 15 to 32 mg ml 21, respectively. The combined treatment of AgNPs with atmospheric pressure-air cold plasma (APACP) induced a drop in the MIC 50 and MIC 100 values of AgNPs reaching 3-11 and 12-23 mg ml 21, respectively, according to the examined species. Epidermophyton floccosum was the most sensitive fungus to AgNPs, while Trichophyton rubrum was the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Lux et al reported that nail plate abrasion, refreshment, and NTP improved fungal removal by 85.7% [139]. The combined treatment with silver nanoparticles and NTP jet decreased the minimum inhibitory concentration of silver nanoparticles [143]. NTP can be combined with other drugs to kill live fungi of some skin diseases, such as body moss and chronic wounds [163].…”
Section: Inactivation Of Fungi In Medicinementioning
confidence: 99%
“…Lux et al reported that nail plate abrasion, refreshment, and NTP improved fungal removal by 85.7% [139]. The combined treatment with silver nanoparticles and NTP jet decreased the minimum inhibitory concentration of silver nanoparticles [143]. NTP can be combined with other drugs to kill live fungi of some skin diseases, such as body moss and chronic wounds [163].…”
Section: Inactivation Of Fungi In Medicinementioning
confidence: 99%
“…It typically manifests as a red, itchy, scaly, and circular rash. Recently, there have been several in vitro ( 71 , 72 ) and in vivo ( 73 , 74 ) studies exploring CAP’s antifungal potential. Scholtz et al.…”
Section: Treatment Of Skin Disease Using Capmentioning
confidence: 99%
“…They found that the fungal cell wall had been damaged under the scanning electron microscope, which indicated that CAP exhibited therapeutic effects in inhibiting fungal growth. Furthermore, they also indicated that the CAP could ameliorate symptoms of fungal skin diseases by the generation of NO, which could inhibit the activity of fungal spores via reducing the activity of keratinase and increasing the mycelium permeability (43). Generally speaking, ROS and RNS from CAP could destroy fungal spores and the integrity of cell membrane to inhibit the growth of fungus.…”
Section: Fungus and Virusmentioning
confidence: 99%